Early-Onset Autoimmune Disease as a Manifestation of Primary Immunodeficiency - Carneiro-Sampaio, Magda; Coutinho, Antonio (Frontiers in Immunology, 2015)
Abstract Autoimmune disorders (AID) have been increasingly observed in association with monogenic primary immunodeficiencies (PID). Here we discuss the interface between PID and AID, focusing on autoimmune manifestations early in life, which could be diagnostic clues for underlying PIDs. Early-onset inflammatory bowel disease has been associated with IL-10 and IL-10R deficiencies, chronic granulomatous disease, IPEX (Immunedysregulation-Polyendocrinopathy-Enteropathy-X-linked), autoinflammatory disorders and others. Some PIDs have been identified as underlying defects in juvenile systemic lupus erythematosus: C1q-, IgA-, IgM deficiencies, IFN- pathway alterations (in Aicardi–Goutières syndrome due to TREX1 mutation). IPEX, due to FOXP3 mutation leading to Treg cell deficiency, usually appearing in the first months of life, was recently observed in miscarried fetuses with hydrops who presented with CD3+ infiltrating lymphocytes in the pancreas. HLH (hemophagocytic lymphohistiocytosis) due to perforin deficiency was also identified as a cause of fetal hydrops. In conclusion, PID should be suspected in any infant with signs of autoimmunity after excluding transferred maternal effects, or in children with multiple and/or severe AID.